Race as a Predictor of Palliative Care Referral Time, Hospice Utilization, and Hospital Length of Stay: A Retrospective Noncomparative Analysis. (January 2018) - Worster, Brooke; Bell, Declan Kennedy; Roy, Vibin; Cunningham, Amy; LaNoue, Marianna; Parks, Susan
Background: Palliative care is associated with significant benefits, including reduced pain and suffering, an increased likelihood of patients dying in their preferred location, and decreased health-care expenditures. Racial and ethnic disparities are well-documented in hospice use and referral patterns; however, it is unclear whether these disparities apply to inpatient palliative care services. Objective: To determine if race is a significant predictor of time to inpatient palliative care consult, patient enrollment in hospice, and patients' overall hospital length of stay among patients of an inpatient palliative care service. Design: Retrospective noncomparative analysis. Setting: Urban academic medical center in the United States. Patients: 3207 patients referred to an inpatient palliative care service between March 2006 and April 2015. Measurements: Time to palliative care consult, disposition of hospice/not hospice (excluding patients who died), and hospital length of stay among patients by racial (Asian, black, Native American/Eskimo, Hispanic, white, Unknown) and ethnic (Hispanic/Latino, non-Hispanic, Unknown) background. Results: Race was not a significant predictor of time to inpatient palliative care consult, discharge to hospice, or hospital length of stay. Similarly, black/white, Hispanic/white, and Asian/white variables were not significant predictors of hospice enrollment ( P s > .05). Limitations: Study was conducted at 1 urban academic medical center, limiting generalizability; hospital race and ethnicity categorizations may also limit interpretation of results. Conclusions: In this urban hospital, race was not a predictor of time to inpatient palliative care service consult, discharge to hospice, or hospital length of stay. Confirmatory studies of inpatient palliative care services in other institutions are needed.